Sex differences in the dorsolateral telencephalon correlate with home range size in blenniid fish - Costa, Silvia S. (2012)
Blenniid fish exhibit a polygynandric mating system with parental care restricted to males. Nest-holder males defend a breeding territory centered on their nest, usually a crevice or hole in a rocky substrate, to which they attract females to spawn. Females, on the other hand, must search for nests in order to spawn and usually are the choosy sex, producing several sequential egg batches and broods during the breeding season. Therefore, male blennies are more site-attached than females. This situation offers an opportunity to investigate potential neural correlates of intraspecific differences in selective pressures for different spatial abilities in these species. Since the dorsolateral telencephalon has been considered a teleost homologue of the mammalian hippocampus, we predicted that the spatial abilities required for females to locate and return accurately to nests of males may have produced a sex difference in the size of the telencephalic nuclei involved in spatial abilities, biased towards females. To test this hypothesis, we assessed the home ranges and measured the size of the dorsolateral telencephalon of both sexes during the breeding season in two blenniid species, the shanny (Lipophrys pholis) and the Azorean rock-pool blenny (Parablennius parvicornis) . We chose these two species because they differ in the degree of chemical communication they use, and this could also lead to differences in telencephalic areas. As predicted, in both species females present considerably larger home ranges paralleled by larger dorsolateral ventral telencephalic nuclei (DLv) than males. Other telencephalic nuclei that were measured did not show any sex difference in size. These results suggest that the DLv is involved in spatial abilities in blenniid fish and that sexual selection may be promoting this divergence as already described for mammals and birds.